INFLUENCE OF HCL 0.02 M ON PHASE AND SIZE OF CaCO3 VIA FINE BUBBLE DIFFUSER METHOD AS DENTAL BIOMATERIAL - Febrida, Renny; Setyanagari, Sekar Diva; Faza, Yanwar (Universitas Baiturrahmah, 2023)
Background. Particles of calcium carbonate (CaCO3) have been applied in a number of fields, including as dental biomaterial. Because CaCO3 particles have three distinct polymorphs and complex crystallization behavior, it is difficult to systematically adjust their physical properties for desired applications. Objective. This investigation aims to examine the influence of the addition of the 0.02 M HCl additive on the phase and size of the CaCO3 particles synthesized with the fine bubble diffuser method. Methods. The type of research is descriptive explorative. There were two sample groups in this study, and each group had three replications (n = 3). Group 1 added 0.02 M of HCl as an addition to the as-prepared material, while Group 2 added no HCl at all. The phase of CaCO3 was evaluated by using the FTIR (Thermo Scientific Nicolet iS5), while the particle size was measured via DLS (Horiba Scientifica SZ-100 Nanopartica) Result. The results showed the sample of CaCO3 without any additive posesses Amorphous Calcium Carbonate (ACC) and calcite. Meanwhile, sample of CaCO3 with addition of HCL 0.02 M showed ACC, calcites and vaterite phase. Particle size of CaCO3 without additve is larger than another one. Conclusion. In this study, the addition of the additive HCl 0.02 resulted in a decrease in the pH of the solution resulting in a phase change from clacite to vaterite as well as decreasing the particle size of CaCO3.